A preparation process of highly flame-retardant fiberboard

By modifying the wood fibers, pretreatment is performed using a mixture of ethanol-acetic acid-water, and combining acidic sodium chlorite and alkaline solution to remove lignin, increasing porosity, and combining bentonite dispersion with cellulose, the existing fiberboard density and strength are solved, and high flame retardant and high performance fiberboard preparation is achieved.

CN116442345BActive Publication Date: 2025-04-15CENTRAL SOUTH UNIVERSITY OF FORESTRY AND TECHNOLOGY +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310405756.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-14
Publication Date
2025-04-15
Estimated Expiration
2043-04-14

AI Technical Summary

Technical Problem

In the existing fiberboard preparation process, lignocellulose has low purity, resulting in poor density and strength performance.

Method used

A high flame retardant fiberboard preparation process is adopted, and wood fibers are modified, and pretreated with a mixture of ethanol-acetic acid-water. Then, acidic sodium chlorite and alkaline solution are used to step-by-step remove lignin, increase porosity, and combine with cellulose through bentonite dispersion to improve connectivity and compatibility, and finally heat-pressing treatment is carried out under high temperature and high pressure conditions.

Benefits of technology

The density, strength and flame retardant properties of the fiberboard are improved, which significantly improves the overall performance of the fiberboard.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116442345B_ABST
    Figure CN116442345B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation process of a highly flame-retardant fiberboard, comprising: pre-treating wood with acetic acid-ethanol to hydrolyze it with acid to obtain residual solids mainly having a cellulose crystal structure; performing multi-gradient delignification treatment on the residual solids mainly having a cellulose crystal structure according to the lignin content thereof by using acidic sodium chlorite and alkaline substances to obtain cellulose; mixing the cellulose with a bentonite dispersion liquid to which a flame retardant is added; adding water, a dispersant and a flame retardant to the bentonite dispersion liquid and stirring it at a high speed to obtain a uniform texture; and after being treated with high temperature and high pressure, the bentonite dispersion liquid has high strength and flame retardancy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fiberboard manufacturing, and in particular to a preparation process of a highly flame-retardant fiberboard. Background Art

[0002] Fiberboard, also known as density board, is a man-made board made of wood fiber or other plant fiber as raw materials, with urea-formaldehyde resin or other suitable adhesives. Adhesives and (or) additives can be applied during the manufacturing process of fiberboard. Fiberboard has the advantages of uniform material, small vertical and horizontal strength difference, and not easy to crack, and has a wide range of uses.

[0003] In the prior art, in the preparation process of fiberboard, strong alkali is mostly used to directly extract cellulose from wood. The cellulose extracted by this method has low purity, so that its density and strength properties are not strong. Summary of the invention

[0004] The invention overcomes the shortcomings of the prior art and provides a process for preparing a highly flame-retardant fiberboard.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: a process for preparing a highly flame-retardant fiberboard, comprising:

[0006] S1: weighing wood fiber and a mixture of ethanol-acetic acid-water, adding all of them into a reaction kettle for heating and heat preservation treatment, cooling to room temperature, filtering, washing, and drying;

[0007] S2: The dried product in S1 and the mixed solution of acetic acid and sodium chlorite are placed in a reaction flask, an inert gas is introduced into the reaction flask, and the mixture is treated at 70° C.-80° C. for 70 min-80 min, and then filtered, washed and dried again;

[0008] S3: adding the dried product in S2 and the alkaline solution into a bottle at a solid-liquid ratio of 1:25, and mixing them, then introducing an inert gas into the bottle, treating at 70°C-80°C for 70min-80min, and then filtering, washing, and drying again;

[0009] S4: immersing the dried product in S3 into a bentonite dispersion having a solid-liquid ratio of 1:100, and immersing the mixture in a vacuum impregnation device at a pressure of 300 Pa-330 Pa for 10 h-12 h, followed by filtering and drying;

[0010] S5: placing the product in S4 in a mold and performing a hot pressing treatment under high temperature and high pressure conditions for 8-10 hours to obtain a highly flame retardant fiberboard.

[0011] In a preferred embodiment of the present invention, the solid-to-liquid ratio of the wood fiber to the mixed liquid in S1 is 1:10, the mass fraction of ethanol is 45%, and the mass fraction of acetic acid is 1%.

[0012] In a preferred embodiment of the present invention, the multiple washing in S1 is to repeatedly rinse the mixture with a 70wt% ethanol solution, then rinse it with distilled water, and finally dry it at a temperature of 105±3°C.

[0013] In a preferred embodiment of the present invention, the product of S1 after drying in S2 has a solid-liquid ratio of 1:25 with the mixed solution of acetic acid and sodium chlorite, while the ratio of acetic acid solution to sodium chlorite solution is 1:1.

[0014] In a preferred embodiment of the present invention, the two alkaline solutions in S3 are mixed, the first mixing is performed using a weak base, and the second mixing is performed using a strong base.

[0015] In a preferred embodiment of the present invention, in S3, the strong base is one or more of sodium hydroxide solution, calcium hydroxide solution, and ammonia water.

[0016] In a preferred embodiment of the present invention, the bentonite dispersion in S4 has a concentration of 8%wt.

[0017] In a preferred embodiment of the present invention, in the high temperature and high pressure in S5, the high temperature is processed at a temperature of 110° C.-130° C., and the high pressure is processed at a pressure of 2 MPa-4 MPa.

[0018] In a preferred embodiment of the present invention, the washing in S2-S5 is performed in a two-time repeated rinsing mode, first washing with 70%wt ethanol and then washing with double distilled water, and the drying in S2-S5 is performed at a temperature of 100°C-110°C.

[0019] In a preferred embodiment of the present invention, the bentonite dispersion is obtained by adding water, a dispersant and a flame retardant to bentonite and stirring the mixture at a high speed.

[0020] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0021] (1) The present invention is a process for preparing a highly flame-retardant fiberboard, which comprises modifying wood fibers from which lignin has been removed, using different acidic and alkaline compounds at different stages to remove hemicellulose and lignin in a step-by-step manner, and increasing the porosity thereof. The fibers are used as a skeleton, and bentonite containing a flame retardant is used as a bridge to connect the fibers. The bentonite is dispersed in the form of a solution into the gaps between the wood fibers, thereby improving the connectivity and compatibility between the wood fibers, thereby increasing the overall density, strength, and flame retardancy.

[0022] (2) The present invention removes lignin twice using different alkalinity strengths, and the synergistic effect of strong alkali and weak alkali removes different lignin molecular weight gradients, further removes lignin, and increases the proportion of cellulose. The second use of strong alkali causes saponification inside, resulting in a decrease in ester bonds and an increase in the molecular gaps between the raw materials, thereby increasing the internal surface area and allowing the bentonite to be evenly combined with the cellulose.

[0023] (3) The present invention uses ethanol-acetic acid alkaline pretreatment, uses ethanol extraction to remove the extract, and then uses acetic acid and hemicellulose to undergo acid hydrolysis at high temperature to extract the hemicellulose. This method can greatly increase the degree of degradation of hemicellulose into monosaccharides or oligosaccharides, which is much higher than the dilute acid hydrolysis process. Therefore, while effectively extracting hemicellulose, it can also effectively avoid the generation of by-products that are harmful to fermentation during dilute acid hydrolysis.

[0024] (4) The present invention first uses an acidic sodium chlorite solution to produce high-purity chlorine dioxide under the action of inert gas and acidic environment, thereby selectively removing lignin, and then selecting different alkaline compounds to react according to the amount of lignin content, thereby performing two different delignification operations with different effects, thereby making the acid and alkali produce a synergistic effect and effectively removing most of the lignin.

[0025] (5) The present invention uses alkali to treat the wood fiber raw material, so that the alkali has a saponification effect on the ester bonds between hemicellulose and other components, thereby reducing the ester bonds, increasing the porosity of the raw material, and increasing the internal surface area, so that the bentonite dispersion is dispersed in the form of a solution into the gaps between the wood fibers, thereby improving the connectivity and compatibility between the wood fibers, thereby achieving the effect of increasing the overall density, increasing the strength, and improving the flame retardancy. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 is a flow chart of a preferred embodiment of the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0030] like Figure 1 As shown, a process for preparing a highly flame-retardant fiberboard comprises:

[0031] S1: weigh a small amount of wood fiber and a mixture of ethanol-acetic acid-water, add all of them into a reactor for heating and heat preservation treatment, cool to room temperature, take out the mixture, filter it, wash it several times, and finally dry it;

[0032] In a preferred embodiment of the present invention, the solid-to-liquid ratio of the wood fiber to the mixed liquid in S1 is 1:10, the mass fraction of ethanol is 45%, and the mass fraction of acetic acid is 1%.

[0033] In a preferred embodiment of the present invention, the multiple washing in S1 is to repeatedly rinse the mixture with a 70wt% ethanol solution, then rinse it with distilled water, and finally dry it at a temperature of 105±3°C.

[0034] It should be noted that ethanol extraction can be used to remove the extract, while acetic acid can degrade hemicellulose into monosaccharides or oligosaccharides, which are then dissolved into the extract; the wood fiber and the mixed solution of ethanol-acetic acid-water are all loaded into the reactor for high-temperature and high-pressure treatment at a heating temperature of 200°C and a holding time of 1 hour. During the high-temperature and high-pressure treatment, acid hydrolysis occurs in the reactor, so that the solid is hydrolyzed and the residual solid is mainly a cellulose crystalline structure, thereby obtaining a hydrolyzate of glucose, which is then filtered to obtain a residual solid mainly having a cellulose crystalline structure, and then a 70wt% ethanol solution is used for the first washing to further remove the acid hydrolysis residue on the surface of the residual solid with ethanol, and then the residual solid is washed with distilled water, and finally dried at a temperature of 100°C-110°C.

[0035] S2: The dried product in S1 and the mixed solution of acetic acid and sodium chlorite are placed in a reaction flask, an inert gas is introduced into the reaction flask, and the mixture is treated at 70° C.-80° C. for 70 min-80 min, and then filtered, washed and dried again;

[0036] In a preferred embodiment of the present invention, the product of S1 after drying in S2 has a solid-liquid ratio of 1:25 with the mixed solution of acetic acid and sodium chlorite, while the ratio of acetic acid solution to sodium chlorite solution is 1:1.

[0037] It should be noted that the acetic acid solution and the sodium chlorite solution are mixed in a ratio of 1:1 to obtain an acidic sodium chlorite solution, and then the product in S1 is placed in the acidic sodium chlorite solution in a ratio of 1:25. The acidic sodium chlorite solution produces high-purity chlorine dioxide under the action of inert gas and acidic environment and at a temperature of 70°C-80°C, thereby destroying the structure of the tight cell wall and breaking the ether bonds between the lignin, while not reacting with cellulose, thereby selectively removing the lignin.

[0038] S3: adding the dried product in S2 and the alkaline solution into a bottle at a solid-liquid ratio of 1:25, and mixing the alkaline solution twice, then passing an inert gas into the bottle, treating at 70°C-80°C for 70min-80min, and then filtering, washing, and drying again;

[0039] In a preferred embodiment of the present invention, the two alkaline solutions in S3 are mixed, the first mixing is performed with a weak base, and the second mixing is performed with a strong base.

[0040] The weak base is an alkaline hydrogen peroxide solution, and in S3, the strong base solution is one or more of a sodium hydroxide solution, a calcium hydroxide solution, and ammonia water, preferably a sodium hydroxide solution.

[0041] The mass ratio of the alkaline hydrogen peroxide solution to the sodium hydroxide solution in the present invention is 2:1.

[0042] It should be noted that in the two alkaline solution mixings in S3, a weak base is used for the first mixing and a strong base is used for the second mixing. When a weak base is used for the first mixing, the weak base has a saponification effect on the ester bonds between hemicellulose and other components. The reduction of ester bonds leads to an increase in the porosity of the raw material and an increase in the internal surface area. In addition, the alkaline solution has a strong delignification effect, thereby removing most of the lignin. However, wood fibers contain various types of lignin with different molar masses. When a weak base is used for the first time, only most of the lignin can be removed, and a small part of other types of lignin still remains and needs to be removed by a strong base, so that alkaline substances are used again for alkaline removal, and thus a strong base is used for the second time to remove the lignin.

[0043] It should be noted that the product after S2 drying is cellulose crystals with some lignin removed. This part of cellulose crystals still contains some lignin. It is put into a bottle with alkaline hydrogen peroxide solution at a solid-liquid ratio of 1:25, and then an inert gas is introduced to react at 70°C-80°C. At this time, the alkalinity is alkali, which has a saponification effect on the ester bonds between hemicellulose and other components. The reduction of ester bonds leads to an increase in the porosity of the raw material and an increase in the internal surface area. In addition, the alkaline solution has a strong delignification effect. As the alkalinity increases, its delignification ability is also enhanced. In S2, the product has been treated in an acidic environment, which destroys the cell wall structure and removes some lignin. In S3, it is treated again with an alkaline compound, so that different alkaline solutions can be added according to the lignin content, so that the acid and alkali can achieve a synergistic effect to remove lignin. After the lignin is removed from the raw material, the enzymatic hydrolysis saccharification rate is significantly improved.

[0044] S4: immersing the dried product in S3 into a bentonite dispersion having a solid-liquid ratio of 1:100, and immersing the mixture in a vacuum impregnation device at a pressure of 300 Pa-330 Pa for 10 h-12 h, followed by filtering and drying;

[0045] In a preferred embodiment of the present invention, the bentonite dispersion in S4 has a concentration of 8%wt.

[0046] In a preferred embodiment of the present invention, the bentonite dispersion is obtained by adding water, a dispersant and a flame retardant to bentonite and stirring the mixture at a high speed.

[0047] It should be noted that the bentonite dispersion has a uniform texture with small particles. After the product of S3 is immersed in the bentonite dispersion, it is impregnated at a pressure of 300Pa-330Pa in a vacuum impregnation device for 10 to 12 hours, so that the dried product in S3 is completely mixed with the bentonite dispersion, and then filtered and dried.

[0048] S5: placing the product in S4 in a mold and performing a hot pressing treatment under high temperature and high pressure conditions for 8-10 hours to obtain a highly flame retardant fiberboard.

[0049] In a preferred embodiment of the present invention, in the high temperature and high pressure in S5, the high temperature is processed at a temperature of 110° C.-130° C., and the high pressure is processed at a pressure of 2 MPa-4 MPa.

[0050] It should be noted that the mixed product obtained by S4 is subjected to high temperature and high pressure treatment at 110°C-130°C and 2MPa-4MPa for 8-10 hours, so that the internal structure of the obtained fiberboard is more tightly fitted, thereby making its overall density higher and its strength increased, thereby improving its flame retardant properties.

[0051] In a preferred embodiment of the present invention, the washing in S2-S5 is performed in a two-time repeated rinsing mode, first washing with 70%wt ethanol and then washing with double distilled water, and the drying in S2-S5 is performed at a temperature of 100°C-110°C.

[0052] Embodiment 1

[0053] A high flame retardant fiberboard preparation process, comprising:

[0054] S1: weigh a small amount of wood fiber and a mixture of ethanol-acetic acid-water, add all of them into a reactor for heating and heat preservation treatment, cool to room temperature, take out the mixture, filter it, wash it several times, and finally dry it;

[0055] S2: The dried product in S1 and the mixed solution of acetic acid and sodium chlorite are placed in a reaction flask, an inert gas is introduced into the reaction flask, and the mixture is treated at 70° C.-80° C. for 70 min-80 min, and then filtered, washed and dried again;

[0056] S3: adding the dried product in S2 and the alkaline solution into a bottle at a solid-liquid ratio of 1:25, and mixing them, then introducing an inert gas into the bottle, treating at 70°C-80°C for 70min-80min, and then filtering, washing, and drying again;

[0057] S4: immersing the dried product in S3 into a bentonite dispersion having a solid-liquid ratio of 1:100, and immersing the mixture in a vacuum impregnation device at a pressure of 300 Pa-330 Pa for 10 h-12 h, followed by filtering and drying;

[0058] S5: placing the product in S4 in a mold and performing a hot pressing treatment under high temperature and high pressure conditions for 8-10 hours to obtain a highly flame retardant fiberboard.

[0059] The high flame retardant fiberboard preparation process pre-treats wood with acetic acid-ethanol to cause acid hydrolysis to obtain residual solids mainly having a cellulose crystal structure, and then uses acidic sodium chlorite and alkaline substances to perform multi-gradient delignification treatment on the residual solids mainly having a cellulose crystal structure according to the lignin content, thereby obtaining cellulose, and then the cellulose is mixed with a bentonite dispersion liquid added with a flame retardant, and the bentonite dispersion liquid is added with water, a dispersant and a flame retardant and stirred at a high speed, so that the texture is uniform, and after being treated with high temperature and high pressure, it has high strength and flame retardancy.

[0060] When using alkaline solution for delignification, hydrogen peroxide solution is first used for treatment. Lignin can be divided into three types of lignin according to its composition differences: lignin, lignin-sinapyl lignin, and lignin-sinapyl lignin-p-hydroxybenzene lignin. Among them, due to the characteristics of the molecular structure of lignin-sinapyl lignin monomers, it is more difficult to remove and has a lower content. Therefore, after using weak alkaline solution hydrogen peroxide to remove most of the other lignin, strong base sodium hydroxide is used to dissolve it. After the combined treatment of weak base and strong base, the reducing sugar concentrations are 50g / L, 60g / L and 90g / L, respectively, thereby removing the lignin.

[0061] Embodiment 2

[0062] On the basis of Example 1, the present invention further provides a method for preparing a bentonite dispersion, comprising the following steps:

[0063] A1: Put bentonite into WF-40 pulverizer for pulverization, take out the pulverized bentonite and put it into a bucket, then pour water into the bucket, the solid-liquid ratio of water to bentonite is 3:10;

[0064] A2: Add polymer dispersant and flame retardant into the barrel of A1, and then stir with a folding stirrer at a speed of 1000r / min-2000r / min for 30min-60min, then pour out and dry;

[0065] A3: The dried mixture of A2 is placed in a mold and treated at a high temperature and high pressure of 3MPa-5MPa and 130℃-150℃ to obtain highly flame-retardant bentonite;

[0066] A4: The highly flame-retardant bentonite obtained in A3 was crushed again using a WF-40 crusher, and then water was added to the powdered highly flame-retardant bentonite at a solid-liquid ratio of 1:100 to obtain bentonite liquid.

[0067] A5: Add the polymer dispersant and the flame retardant to the bentonite liquid obtained in A4, and then stir it again using the hinged stirrer to obtain a 8 wt % bentonite dispersion with a uniform texture.

[0068] The mixed solution of ethanol-acetic acid-water in S1 is replaced with the dilute acid hydrolysis process in the existing technology to extract hemicellulose. However, the yield of the dilute acid hydrolysis sugar process is low and will cause a lot of waste. Studies have shown that adding Fe ions to the dilute acid hydrolyzate can increase the saccharification yield, but the Fe ions still need to be removed later, the steps are complicated, and by-products that are harmful to fermentation, such as furfural and organic acids, are generated during the hydrolysis process.

[0069] The entire step of using the mixed solution of acetic acid and sodium chlorite in S2 is removed, and the product in S1 is directly subjected to the operation of S3. Since the ether bonds between lignin are not broken by the influence of chlorine dioxide, the alkaline compounds can only saponify the ester bonds between hemicellulose and other components, resulting in an increase in the porosity of the raw material. Therefore, the hemicellulose can only be removed again, and part of the lignin can be removed, so that the obtained cellulose is not pure enough and has more impurities, and the acid-base synergistic effect cannot be produced.

[0070] The entire step of treating the dried product in S2 with an alkaline compound in S3 is removed, so that the alkaline compound will not saponify the ester bonds between hemicellulose and other components, thereby reducing the ester bonds, increasing the porosity of the raw material, and increasing the internal surface area. When subsequently mixed with the S4 bentonite dispersion, the bentonite is difficult to disperse in the form of a solution into the gaps between the wood fibers, thereby failing to improve the connectivity and compatibility between the wood fibers.

[0071] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. A process for preparing a highly flame-retardant fiberboard, characterized in that: include: S1: weighing wood fiber and a mixture of ethanol-acetic acid-water, adding all of them into a reaction kettle for heating and heat preservation treatment, cooling to room temperature, filtering, washing, and drying; S2: Put the product in S1, acetic acid and sodium chlorite into a reaction bottle, introduce inert gas into the reaction bottle, treat at 70° C.-80° C. for 70 min-80 min, and then filter, wash and dry again; S3: adding the dried product in S2 and the alkaline solution into a bottle at a solid-liquid ratio of 1:25, and mixing the alkaline solution twice, then passing an inert gas into the bottle, treating at 70°C-80°C for 70min-80min, and then filtering, washing, and drying again; S4: Immerse the dried product in S3 into a bentonite dispersion and immerse it in a vacuum impregnation device at a pressure of 300Pa-330Pa for 10h-12h, then filter and dry; S5: placing the product in S4 in a mold and performing a hot pressing treatment under high temperature and high pressure for 8-10 hours to obtain a highly flame retardant fiberboard; The two alkaline solutions in S3 are mixed, the first mixing is performed with a weak base, and the second mixing is performed with a strong base; The bentonite dispersion in S4 is a bentonite dispersion with a concentration of 8%wt; The high temperature and high pressure in S5 is processed at a temperature of 110°C-130°C, and the high pressure is processed at a pressure of 2MPa-4MPa; After drying in S2, the solid-liquid ratio of the product of S1 to the mixed solution of acetic acid and sodium chlorite is 1:25, while the ratio of the acetic acid solution to the sodium chlorite solution is 1:1; The weak base is an alkaline hydrogen peroxide solution, and the strong base solution is one or more of a sodium hydroxide solution, a calcium hydroxide solution, and ammonia water.

2. The process for preparing a highly flame-retardant fiberboard according to claim 1, characterized in that: The solid-to-liquid ratio of the wood fiber to the mixed liquid in the S1 is 1:10, the mass fraction of ethanol is 45%, and the mass fraction of acetic acid is 1%.

3. The process for preparing a highly flame-retardant fiberboard according to claim 1, characterized in that: The washing in S1 is to repeatedly rinse the mixture with a 70 wt % ethanol solution, then rinse it with distilled water, and finally dry it at a temperature of 105±3° C.

4. The process for preparing a highly flame-retardant fiberboard according to claim 1, characterized in that: The washing in S2-S3 is performed by two repeated rinses, first washing with 70%wt ethanol and then washing with double distilled water. The drying in S2-S4 is performed at a temperature of 100°C-110°C.

5. The process for preparing a highly flame-retardant fiberboard according to claim 1, characterized in that: The bentonite dispersion is obtained by adding water, a dispersant and a flame retardant to bentonite and stirring at high speed.

Citation Information

Patent Citations

  • Method used for extracting hemicellulose with low pigment content

    CN105440166A

  • Production method of flame-retardant fiber board

    CN106638072A

  • Fireproof wood treatment method

    CN111844300A

  • Preparation method of environment-friendly high-strength wood composite material

    CN115635555A